The prevalence of hand and wrist osteoarthritis in elite former cricket and rugby union players. Issue 8 (August 2019) - Jones, Mary E.; Davies, Madeleine A.M.; Shah, Karishma; Kemp, Simon; Peirce, Nick; Leyland, Kirsten M.; Stokes, Keith A.; Judge, Andrew D.; Newton, Julia L.; Furniss, Dominic; Arden, Nigel K.
Abstract: Objectives: This study aimed to determine the prevalence of hand and wrist osteoarthritis in former elite cricket and rugby union players, by sport and playing position, and to define the prevalence of severe hand injury, and its association with hand osteoarthritis. Design: Cross-sectional. Methods: Data from cross-sectional studies of former elite male cricket and rugby players were used to determine the prevalence of hand pain, physician-diagnosed osteoarthritis, and previous severe injury. Multivariable logistic regression was used to determine the association of previous injury with pain and osteoarthritis. Results: Data from 200 cricketers and 229 rugby players were available. Complete case analysis resulted in 127 cricketers and 140 rugby players. Hand pain was more prevalent amongst cricketers (19.7%) than rugby players (10.0%). The prevalence did not differ between cricket and rugby players for hand osteoarthritis (2.4% and 3.6%), wrist osteoarthritis (1.6% and 2.1%), or previous severe hand injury (36.2% and 31.4%). No significant association between previous hand injury and pain or osteoarthritis was identified in either sport. Conclusions: Former elite cricketers reported more hand pain than rugby players. No significant association was found between self-reported severe injury and hand osteoarthritis in either cohort, potentially indicating that risk factors aside from injury may be more prominent in the development of hand osteoarthritis.